(untitled) (Progressive Agriculture, 2019)
Responses in photosynthesis, transpiration, stomatal conductance, chlorophyll fluorescence characteristics and chlorophyll content of four maize (Zea mays L.) genotypes were examined under first phase of salt stress. In the experiment four maize genotypes viz. indigenous yellow pure line, indigenous yellow, hybrid, and indigenous white were tested in two levels of salinity (control: without NaCl application; salinity: 12 dS m-1 by applying NaCl). The experiment was laid out following completely randomized design (CRD) with four replications in the net house of Department of Crop Botany, Bangladesh Agricultural University, Mymensingh. Plants were harvested on day 21 after 7 d application of full salt stress (12 dS m-1). The reductions of shoot fresh masses under salinity were 70, 57, 55 and 61% in indigenous yellow pure line, indigenous yellow, hybrid, and indigenous white, respectively. Some core physiological parameters viz. net photosynthesis rate (Pn), transpiration rate (E), stomatal conductance (gs), and the chlorophyll content decreased in all the maize genotypes except indigenous white under first phase of salt stress. In contrast, the ratio of variable ﬂuorescence to maximal ﬂuorescence (Fv/Fm) of photosystem II significantly decreased only in indigenous yellow pure line under salinity stress. Thus the first phase of salt stress seemed to be deleterious on its response to shoot fresh mass production in all the tested four maize genotypes with the concomitant decrease in rate of photosynthesis, rate of transpiration, stomatal conductance and chlorophyll content in all genotypes except indigenous white. Progressive Agriculture, Vol. 30, Suppl. 1: 26-32, 2019